Frontal-subcortical dysfunction in toxic oil syndrome: a proof-of-concept eye-tracking and cognitive study four decades after exposure - Benito-León, Julián; Lapeña-Motilva, José; Ruiz-Ortiz, Mariano; Doniger, Glen M.; Álvarez-Sesmero, Sonia; de Béjar, Verónica Giménez; Nogales, María Antonia; Morales, Montserrat; Mondal, Ritwick; Deb, Shramana; Bartolomé, Fernando; Alquézar, Carolina; et al. (Frontiers in Neuroscience, 2025)
IntroductionToxic Oil Syndrome (TOS) emerged in Spain in 1981 after ingestion of rapeseed oil adulterated with aniline derivatives. More than four decades later, survivors continue to report cognitive complaints, but objective evidence of long-term dysfunction remains limited.MethodsIn this case-control study, 47 TOS survivors and 44 matched healthy controls completed validated eye-tracking paradigms (visually guided, memory-guided, and antisaccade tasks) and a standardized neuropsychological battery. Groups did not differ significantly in age, sex, or education.ResultsTOS survivors showed preserved performance on visually guided and memory-guided saccades, with no group differences in latency, gain, peak velocity, or spatial error (all p > 0.05). In contrast, they exhibited fewer correct antisaccades (mean 3.6 vs. 5.0; p = 0.029), more reflexive saccades (mean 7.0 vs. 5.7; p = 0.033), and increased backward reflexive saccades (mean 6.3 vs. 5.1; p = 0.040). Cognitive testing revealed selective impairments in executive function, attention, and processing speed, with preserved memory. Structural equation modeling confirmed that antisaccade impairment remained significant after adjusting for confounders and demonstrated an independent contribution of attention to correct antisaccade performance.ConclusionFindings indicate persistent frontal-subcortical circuit dysfunction in TOS survivors, consistent with immune- or vascular-mediated injury patterns rather than progressive neurodegeneration. Eye-tracking provides a noninvasive biomarker of latent executive dysfunction and may be useful for long-term monitoring of populations exposed to environmental toxins.